APPLICATION OF A REALISTIC APPROACH TO IMPROVE THE ABILITY OF MATHEMATICAL PROBLEM SOLVING AND SELF REGULATED LEARNING OF JUNIOR HIGH SCHOOL STUDENTS - Rina Krisnawati; Euis Eti Rohaeti; Rippi Maya ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2018)
This study is a quasi-experimental research, which aims to examine the achievement and improvement of problem-solving skills of mathematics and the independence of junior high school students learning through a realistic approach. The population in this study is all students of class VIII SMPN 4 Subang. Samples were taken by random class, obtained two classes of class VIII H as the experimental class and VIII.F as control class. The instrument in this study is a set of mathematical problem-solving test and a set of learning independence scales. The study found that the achievement and improvement of students' mathematical problem-solving ability and the independence of student learning whose learning using realistic learning are better than that of learning using ordinary learning in terms of the initial ability level of students. There is an interaction of mathematical problem-solving abilities between students whose learning uses a realistic approach with a student's initial ability level. Meanwhile, there is no interaction between realistic learning with the level of initial ability of students in generating student self-reliance. Besides, there is no association between mathematical problem solving ability and student learning independence, both in class that use realistic and classroom learning using ordinary learning. The picture of student's performance during realistic learning is more active, it shows the involvement of students both individually and in collaboration with the group, so that it can improve the problem solving ability of mathematics as well as student's learning independence. The description of the students' difficulties in solving the problem of mathematical problem solving ability lies in the indicator about number 5 which is about making the mathematical model because of the lowest percentage indicator.